2013
DOI: 10.3762/bjoc.9.298
|View full text |Cite
|
Sign up to set email alerts
|

IBD-mediated oxidative cyclization of pyrimidinylhydrazones and concurrent Dimroth rearrangement: Synthesis of [1,2,4]triazolo[1,5-c]pyrimidine derivatives

Abstract: SummaryOxidative cyclization of 6-chloro-4-pyrimidinylhydrazones 4 with iodobenzene diacetate (IBD) in dichloromethane gives rise to [1,2,4]triazolo[4,3-c]pyrimidine derivatives 5a–o. These incipient products undergo feasible Dimroth rearrangement to furnish the isolated [1,2,4]triazolo[1,5-c]pyrimidines 6a–o in moderate to high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It is well‐known that such Dimroth‐type process can be accomplished by heating with acid or base and is facilitated in case of electron‐withdrawing groups introduced into pyridine ring ,. In some cases the rearrangement of pyridine or pyrimidine derivatives occurs under relatively mild conditions, however, in the presence of nucleophiles, such as H 2 O or NH 3 . We found that this interconversion proceeds at room temperature ( 3 f , Scheme 6 and m , Scheme ) as well as on heating in POCl 3 (106 °C, method A ) or in acetic acid (118 °C, method B ).…”
Section: Resultsmentioning
confidence: 96%
“…It is well‐known that such Dimroth‐type process can be accomplished by heating with acid or base and is facilitated in case of electron‐withdrawing groups introduced into pyridine ring ,. In some cases the rearrangement of pyridine or pyrimidine derivatives occurs under relatively mild conditions, however, in the presence of nucleophiles, such as H 2 O or NH 3 . We found that this interconversion proceeds at room temperature ( 3 f , Scheme 6 and m , Scheme ) as well as on heating in POCl 3 (106 °C, method A ) or in acetic acid (118 °C, method B ).…”
Section: Resultsmentioning
confidence: 96%
“…Upon removal of the Boc protecting group, the Dimroth interconversion of 2 gj and 2 jg reoccurred, resulting in their mixture examined by 1 H NMR (Figures S3–4). Therefore, by introducing the fluorophore, 9‐aminoacridine, with the cooperation of 2,4,6‐trifluorophenyl, the thermodynamic Dimroth rearrangement of DAMA was achieved under very mild condition …”
Section: Methodsmentioning
confidence: 99%
“…Wang's group showed 64 that [1,2,4]triazolo [4,3-c]pyrimidine derivatives 44 formed in situ as a result of oxidative cyclization of (6-chloropyrimidin-4-yl)hydrazones 43 by the action of iodobenzene diacetate in CH 2 Cl 2 undergo Dimroth rearrangement with the formation of [1,2,4]triazolo [1,5-c]pyrimidines 45 in moderate (in the case of using propionaldehyde hydrazones) and high (in the case of using substituted benzaldehyde and furfural Thus, the authors of a study 64 proposed a general and convenient method for the synthesis of new derivatives of [1,2,4]triazolo [1,5-c]pyrimidines. The process has several advantages, including good yields, ease of operation, environmental benignness, relatively short reaction times, and the possibility to use a wide range of substrates which makes it a useful and attractive process for the synthesis of structurally diverse triazolopyrimidines.…”
Section: Rearrangement Of Condensed Heterocyclic Systems Containing Five-membered Rings With Three Nitrogen Atomsmentioning
confidence: 99%